KEEFEKTIFAN MEDIA FILM ANIMASI TERHADAP KETERAMPILAN MENULIS CERITA SISWA KELAS V MADRASAH IBTIDAIYAH DARUL ISTIQAMAH PUCE’E KABUPATEN SINJAI - Mutiatul Khaerah; Andi Sukri Syamsuri; Tarman A Arief (STKIP Subang, 2026)
The main problem in this study is the low ability of students in writing stories, which occurs because the implementation in the learning process still tends to use a conventional approach. Teachers mostly apply the lecture method, making learning seem more monotonous. As a result, students' writing skills are not well honed. Teachers often only give writing assignments with little explanation about the rules of good and correct writing, so that students' creativity and imagination are limited. This study aims to determine the effectiveness of animated films on the story writing skills of fifth-grade students at Madrasah Ibtidaiyah Darul Istiqamah Puce'e, Sinjai Regency. The type of research used in this study is a pre-experimental design, which is a type of research that only involves one experimental class without a comparison group. The research design is a One Group Pretest-Posttest Design. The pretest is given before the treatment, and the posttest is given after the treatment. The sample in this study consists of fifth-grade students, comprising 1 male student and 10 female students. Data collection techniques were conducted using tests and observations. The data analysis technique in this study is descriptive and inferential statistical data analysis (t-test). Descriptive statistics show that the average score for story writing skills before the use of animated films was 60.81. Meanwhile, the average score for story writing skills after the use of animated films was 92.90. This shows that there was a difference in students' story writing skills before and after the use of animated films in learning. The t-test analysis results show that the t-count = 12.01 and t-table = 2.228, so t-count = 12.01 > t-table 2.228, which means H1 is rejected and H1 is accepted. Therefore, it can be concluded that animated film media is effective in improving the story writing skills of fifth-grade students at Madrasah Ibtidaiyah Darul Istiqamah Puce'e, Sinjai Regency.